Absorptive capacities as organizational routines: configuration of learning modes for digital technology-based SMEs - Cunha Filho, Marcio Augusto Lassance (2022)
Regardless the size of the company, effectively seeking knowledge on external sources may explain heterogeneity aspects between successful and unsuccessful firms. Digital technology- based SMEs (digital SMEs) run into a particular challenge in this scenario. These organizations commercialize products, services or solutions based on proprietary digital technology - hardware or software. Aditionally to the limited resources when compared to larger organizations, these SMEs must follow closely the current digital technology dynamics in the marketplace. For these reasons, it is imperative to understand in detail the mechanisms, and to develop the abilities to improve the absorptive capacity (ACAP), defined as the organizational ability to identify, assimilate and exploit the knowledge generated by company external sources. Despite the ACAP relevance, scholars are relatively silent when it comes to its operationalization. In an attempt to overcome this limitation, the aim in this thesis project is to examine thoroughly the ACAP operationalization in the context of digital SMEs. The ambition is to uncover the set of learning modes (LM) embedded into the practiced routines of ACAP underpinning this operationalization. In line with this, the main thesis research question is: how learning modes of practiced routines configure the absorptive capacity (ACAP) dimensions in the context of digital technology-based SMEs? This research follows an article-based thesis structure. The first article investigate the ACAP extant literature in search of research fronts of the theme. Employing a bibliographic coupling procedure followed by a content analysis, the aim was to identify the main clusters of research trends in ACAP. The role of knowledge absorption capacity in organizational capabilities, alliance networks, open innovation processes, intra-organizational learning, as well as exploratory and exploitative initiatives are the relevant research fronts identified. Content analysis in this first study revealed a relatively under investigated ACAP research in the context of the digital SMEs. Second and third article tackled this limitation. Employing a qualitative approach with multiple-case study, the second study examined the ACAP configuration through practiced routines in the context of digital SMEs. Seizing on organizational routines as building blocks of ACAP sub-capacities, this exploratory study exposed the practiced routines of knowledge absorption in the context of the digital SMEs. Finally, through an in depth multiple- case exploratory analysis, the third study built on organizational learning and organizational routines literature to investigate the learning modes of the ACAP sub-capacities in digital SMEs. Although built independently, the combined findings in the second and third articles exposed the practiced routines and the learning modes as integrating elements of ACAP. Then, thanks to the theoretical considerations linking findings in both articles, the final ACAP configuration through learning modes embedded in practiced routines for digital SMEs emerges. Theoretical contribution comprises elements in different field of studies. Firstly, it adds to the ACAP literature by shedding light on the practice perspective of the concept by exposing an actual operationalization of the ACAP sub-capacities. Secondly, it also adds to the organizational routines literature by investigating the observable practiced routines of knowledge absorption in this specific context. Finally, it adds to the organizational learning literature by uncovering the preferred manners of learning in digital SMEs. There are management contributions as well. Considerations about the evidence retrieved from the field provide a thorough analysis of the knowledge absorption operationalization endeavors for digital technology-based SMEs. Owners and managers of digital SMEs might leverage these insights to support their strategic decision making processes.